The heat is off! The role of technology attributes and individual attitudes in the diffusion of smart thermostats: Findings from multi-country survey - Gengyang Tu; Corinne Faure; Joachim Schleich; Marie-Charlotte Guetlein (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
Smart thermostats may provide up to 10% savings in residential thermal energy use without loss of comfort, yet their diffusion has typically been slow. To better understand adoption of these devices, we conducted an online survey with approximately 5,500 respondents from eight European countries that included both a discrete choice experiment (DCE) and stated past adoption of smart thermostats. The results we obtained by estimating mixed logit models suggest that households value heating cost savings, remote temperature control, the display of changes in energy consumption, and recommendations by experts, albeit with substantial heterogeneity across countries; in comparison, subsidies are positively valued in all countries except for Germany and Spain, and recommendations by energy providers in all countries except Poland where they are negatively valued. Further, the findings provide evidence that consumer innovativeness reinforces the acceptance of technical attributes (heating cost savings, feedback functionalities, and remote temperature control), that privacy concerns reduce the acceptance of remote functionalities, and that stronger environmental identity reinforces the acceptance of environmentally related attributes (heating cost savings and feedback functionalities). The results we obtained from estimating binary response models of stated past adoption of smart thermostats are generally consistent with those of the DCE.
urn:nbn:de:0011-n-6187442
Keywords: 330; smart thermostats; smart home devices; choice experiment; mixed logit; innovativeness; privacy